2022
DOI: 10.3389/fmicb.2022.853593
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Two Lytic Phages Efficient Against Phytopathogenic Bacteria From Pseudomonas and Xanthomonas Genera

Abstract: Pseudomonas syringae is a bacterial pathogen that causes yield losses in various economically important plant species. At the same time, P. syringae pv. tomato (Pst) is one of the best-studied bacterial phytopathogens and a popular model organism. In this study, we report on the isolation of two phages from the market-bought pepper fruit showing symptoms of bacterial speck. These Pseudomonas phages were named Eir4 and Eisa9 and characterized using traditional microbiological methods and whole-genome sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Aeromonas phage JELG-KS1 has demonstrated a conserved modular genome organization typically seen in other subfamily Studiervirinae podophages (e.g., Chatterjeevirus ICP3 [ 85 ], Ningirsuvirus ninurta [ 86 ], Pektosvirus PP81 [ 87 , 88 ], Teseptimavirus T7 [ 89 ], Ghunavirus gh1 [ 90 ]) and tentative Studiervirinae phages such as Pseudomonas phage Eir4 [ 91 ], Hafnia phage Ca [ 92 ], etc. An open reading frame encoding a DNA-directed RNA polymerase, a hallmark of Autographiviridae podophages, was readily identifiable among the first few ORFs at the beginning of the genome, which likely represent early genes.…”
Section: Resultsmentioning
confidence: 99%
“…Aeromonas phage JELG-KS1 has demonstrated a conserved modular genome organization typically seen in other subfamily Studiervirinae podophages (e.g., Chatterjeevirus ICP3 [ 85 ], Ningirsuvirus ninurta [ 86 ], Pektosvirus PP81 [ 87 , 88 ], Teseptimavirus T7 [ 89 ], Ghunavirus gh1 [ 90 ]) and tentative Studiervirinae phages such as Pseudomonas phage Eir4 [ 91 ], Hafnia phage Ca [ 92 ], etc. An open reading frame encoding a DNA-directed RNA polymerase, a hallmark of Autographiviridae podophages, was readily identifiable among the first few ORFs at the beginning of the genome, which likely represent early genes.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest the use of higher phage concentrations to compensate for the reduction of host growth. Another explanation could be the development of slow-growing phage-resistant mutants during infection [ 38 ]. Interestingly, the partial regrowth of BF17-treated bacteria occurred at much higher MOIs (>1) ( Figure 5 c).…”
Section: Resultsmentioning
confidence: 99%
“…Due to this unique feature to phage, phage therapy would not directly affect the density, richness, and viability of other microorganisms living in microecology ( Wang et al, 2019 ; Federici et al, 2021 ). The growth inhibitory curve indicated that the inhibitory ability of MA9V-1 was little weaker than other phages, such as phage P. syringae Eisa9 ( Korniienko et al, 2022 ) and P. aeruginosa phage PPAY ( Niu et al, 2022 ). We hypothesized a reasonable explanation that phage MA9V-1 required a long time to complete adsorption, invasion, proliferation, maturation, and lysis, since it has a lower burst size value (only 10 PFU/cell), which made it not easy to inhibit the bacterial growth.…”
Section: Discussionmentioning
confidence: 99%